Long Feeding High-Fat Diet Induces Hypothalamic Oxidative Stress and Inflammation, and Prolonged Hypothalamic AMPK Activation in Rat Animal Model - Cavaliere, Gina; Viggiano, Emanuela; Trinchese, Giovanna; De Filippo, Chiara; Messina, Antonietta; Monda, Vincenzo; Valenzano, Anna; Cincione, Raffaele I.; Zammit, Christian; Cimmino, Fabiano; Catapano, Angela; Sessa, Francesco; et al. (Frontiers in Physiology, 2018)
Scope: The hypothalamus is a key brain region involved in the control of feeding and energy expenditure. Hypothalamic inflammation and oxidative stress are landmarks of both obesity and aging processes, although the molecular mechanisms are still unknown. Therefore, with the aim to understand the neurobiological mechanisms of energy homeostasis during aging, we evaluate the effects of long feeding high fat diet in rats, at different age, on modulation of hypothalamic molecular pathway, oxidative stress and inflammation. Procedures: Male Wistar rats were divided into two groups: control group, receiving standard diet (CD), and treated group, receiving high fat diet (HFD). Both groups were treated with the appropriate diet for 1, 3, 6, 12, or 18 weeks. We investigated energy balance and body composition, as well as lipid profile, homeostatic model assessment (HOMA) index, and inflammatory state in serum. Furthermore, we also analyzed, at hypothalamic level, inflammation and oxidative stress, and AMPK and pAMPK expression levels. Results: Our data showed that aging and HFD induce increased energy intake and energy efficiency and decreased energy expenditure associated, at hypothalamic level, with inflammation and oxidative stress and activation of AMPK. Conclusion: Our results indicate that the age at which HFD feeding starts and the diet duration is critical in obesity development. The prolonged activation of hypothalamic AMPK may be related to the alterations in energy homeostasis.